2011
DOI: 10.1183/09031936.00148310
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of hospitalisation for right heart failure in pulmonary arterial hypertension

Abstract: The aim of this study was to examine the causes and outcomes of hospitalisation in patients with pulmonary arterial hypertension (PAH).205 consecutive hospitalisations occurring between 2000 and 2009 in 90 PAH patients were studied. The leading causes for hospitalisation were right heart failure (RHF; 56%), infection (16%) and bleeding disorders (8%). For patients with RHF, in-hospital mortality was 14% overall, 46% for patients receiving inotropes and 48% for those admitted to the intensive care unit. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
163
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(177 citation statements)
references
References 39 publications
9
163
1
4
Order By: Relevance
“…Such a strategy would be especially unfortunate in a progressive disease, where these events portend a poor outcome. 22 Our own study showed that patients who eventually died were much more likely to have been hospitalized during the follow-up period. Thus, there is a continuing effort to find an easy-to-measure biomarker that can accurately predict outcomes in these patients so that these outcomes may be prevented.…”
Section: Discussionmentioning
confidence: 83%
“…Such a strategy would be especially unfortunate in a progressive disease, where these events portend a poor outcome. 22 Our own study showed that patients who eventually died were much more likely to have been hospitalized during the follow-up period. Thus, there is a continuing effort to find an easy-to-measure biomarker that can accurately predict outcomes in these patients so that these outcomes may be prevented.…”
Section: Discussionmentioning
confidence: 83%
“…Hospitalization for worsening pulmonary arterial hypertension is costly and is associated with a poor prognosis. [23][24][25] Rates of hospitalization for any cause did not differ significantly among the study groups, although these data were not collected prospectively and are thus subject to some uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…RV failure is the leading cause of hospitalization in PH (42). Some patients rapidly develop RV failure whereas others remain stable, despite similar RV hypertrophy and similar RV pressures (43).…”
Section: Maladaptive Rv Hypertrophymentioning
confidence: 99%